216k views
5 votes
Given the function f(x) = −3x2 + 4x + 6, find f(2) and f(3). Choose the statement that is true concerning these two values.

User Ygg
by
4.6k points

2 Answers

4 votes

For this case we have the following function:


f (x) = - 3x ^ 2 + 4x + 6

We must evaluate the function when
x = 2and
x = 3

For
x = 2:


f (2) = - 3 (2) ^ 2 + 4 (2) +6\\f (2) = - 3 * 4 + 8 + 6\\f (2) = - 12 + 8 + 6

Different signs are subtracted and the major sign is placed.

Equal signs are added and the same sign is placed.


f (2) = - 4 + 6\\f (2) = 2

For
x = 3:


f (3) = - 3 (3) ^ 2 + 4 (3) +6\\f (3) = - 3 * 9 + 12 + 6\\f (3) = - 27 + 12 + 6

Different signs are subtracted and the major sign is placed.

Equal signs are added and the same sign is placed.


f (3) = - 15 + 6\\f (3) = - 9

Answer:


f (2) = 2\\f (3) = - 9

User Dmitry Shilyaev
by
5.1k points
4 votes

Answer:

f(x)= −3x^2 + 4x + 6;

f(2) = 2;

f(3) = -9

Explanation:

You have to substitute the values for the given functions. Remember to use PEDMAS for the order of operations: parentheses, exponents, division, multiplication, addition, and then substitution.

We'll insert 2 for the value of x for the first one.

f(2)= (-3)*2^2 + 4*2 + 6

f(2) = (-3)*4+ 4*2+6

f(2) = -12 + 8 + 6

f(2) = -12 + 14

f(2) = 2

We'll insert 3 for the value of x for the second one.

f(3) = (-3)*3^2+4*3+6

f(3) = (-3)*9+4*3+6

f(3) = -27 + 12 + 6

f(3) = -9

User Tim Tisdall
by
4.5k points